The organizational aspects of corporate and organizational crime - Erp, Judith Gabriël van (Administrative sciences)
Corporate crimes seem endemic to modern society. The newspapers are filled on a daily basis with examples of financial manipulation, accounting fraud, food fraud, cartels, bribery, toxic spills and environmental harms, corporate human rights violations, insider trading, privacy violations, discrimination, corporate manslaughter or violence, and, recently, software manipulation. Clearly, the problem of corporate crime transcends the micro level of the individual "rotten apple": although corporate crimes are ultimately committed by individual members of an organization, they have more structural roots, as the enabling and justifying organizational context in which they take place plays a defining role. Organizations provide individuals with positions, incentives, networks, rules, routines, perceptions and beliefs, that structure the opportunities for crime. Thus, organizational factors can explain how misconduct in organizations is defined, perceived, normalized, organized, and facilitated on the one hand, and controlled and prevented on the other hand. Organization studies have a long tradition of studying misconduct and deviance in organizational contexts. This Special Issue of Administrative Sciences focuses on the organizational and administrative aspects of a broad spectrum of corporate and organizational crimes.